Social capital and community integration in post-disaster relocation settlements after the 2004 Indian Ocean Tsunami in Indonesia - Daly, Patrick (2023)
The permanent relocation of persons from areas threatened by environmental stress is widely seen within the international humanitarian sector as problematic due to negative social and economic impacts. However, relocation is increasingly seen as a likely, if unfortunate, response to climate change as rising sea-levels, changing ecological conditions, and increasingly intense disasters create powerful push factors. The more dramatic examples of environmental migration focus on long-distance movements, including crossing national borders, which raise issues about the importance of social capital for migrants trying to build community cohesion and integrate into different cultural contexts. However, it is likely that most relocation because of environment stress will occur at sub-national to very local geographic scales, similar to what happens after large-scale disasters, meaning that persons might be resettled within familiar cultural, linguistic, and religious contexts. In this paper we use qualitative data collected in 12 resettlement complexes built in Aceh, Indonesia for persons displaced by the 2004 Indian Ocean Tsunami to analyze the importance of social capital for building cohesion within resettlement complexes and between resettlement complexes and host communities. We find that even though tsunami-affected persons were generally relocated less than 20 km from their pre-tsunami homes, there were clear social distinctions between resettled persons and host communities, which had practical impacts on integration, access to resources, and participation within local governance structures. We found shared cultural and religious traditions and social practices served as important sources of bonding capital within resettlement complexes. However, the same attributes were less effective as bridging capital between resettlement complexes and their host communities. These findings show that governments and NGOs need to be cautious about underestimating the negative social disruptions caused by short-distance relocation and the importance of bonding social capital for fostering stable and sustainable resettlement communities.